Graves' disease. Issue 7 (July 2019) - Cheetham, Tim; Boal, Rachel
Abstract: Graves' disease develops when pathogenic thyroid receptor antibodies stimulate the thyroid gland resulting in excessive thyroid hormone production. Children and adolescents with Graves' disease can present in a variety of ways to many different clinical teams with a diverse range of underlying symptoms and signs. Graves' disease is usually managed initially with the anti-thyroid drug (ATD) carbimazole. However, only 20–25 % of young patients remit (remaining euthyroid when the ATD is stopped in the longer term) after a 2 year course of ATD treatment. Some families or patients who relapse then opt for surgery (total thyroidectomy) or radioiodine (RI) rather than returning to ATD. Unfortunately the young person then requires life-long thyroid hormone replacement. This is not an ideal outcome and new therapeutic approaches are needed if patients with Graves' are to spend their adult lives free of daily medication with ATD or thyroxine replacement. This article discusses the known science and offers advice for diagnosis and treatment options.